Penulisan Naskah Dengan Teknik Naratif Dalam Produksi Feature Desa Wisata Kembangarum Sleman “Its My Journey “ - Dyant Fitri Intan Dyatri, Dwi Nurrahmi K., M.Suparwoto (Jurnal Ilmu Komunikasi AKRAB, 2022)
ABSTRACTKembangarum Tourism Village is one of the superior tourist villages located inTuri District, Sleman Regency, seen from the various achievements and advantages of itstourist destinations compared to other tourist villages in the sub-district.Kembangarum Tourism Village, which stands on 22 hectares of land fromresidents' land, the village treasury, which is highly utilized for tourism potential so thatit can drive the local economy. Kembangarum Tourism Village is led by Mr. HeryKustriyatmo and managed by local residents involving 1 RW and 4 RT.The writer as the scriptwriter together with the director and camera personmade the Kembangarum Tourism Village a feature program work entitled "It's MyJourney". In this work the writer applies a narrative script writing technique. Writing ascript using a narrative technique was chosen because it is very appropriate with variedstory ideas and can explain a tour to viewers so that viewers can enjoy and feel euphoriaby watching the tourism feature program in Kembangarum Village hosted by hosts in theprogram.Keywords: Kembangarum tourism village, Featured, Narrative Technique Writing.